Results of the research analysis of the influence of contamination of the working fluid on the reliability of the hydraulic drive - Viunyk, Olha; Khokhlov, D.; В’юник, Ольга Володимирівна (Запоріжжя : 2023, 2023)
EN: The main source of power losses in the hydraulic pump is the technical condition of the couplings of the parts of the pumping assembly. The increased concentration of mechanical impurities in the working fluid accelerates the wear of friction surfaces. The study of the dependence of the wear of gear pumps of the GP-2 type on the concentration of mechanical impurities was carried out by the method of accelerated tests. The pumps were tested in the nominal mode on the working fluid purified by an 8...12 μm filter. Then this liquid was contaminated with grinding powder. When the working fluid was contaminated with M-20 grinding powder with a mass concentration of 0.005%, the volumetric efficiency decreased by 17% in 138 hours.
Keywords: agricultural; construction; hydraulic units; wear of hydraulic units; hydraulic motors; distributors